The Experience Teaching Vocabulary through Storytelling to Students by Using Media Flash Card at Elementry School - Hudzaifah, Ilmiyah (English Education and Literature Journal (E-Jou), 2026)
The purpose of this study is to determine the teaching experience of teachers and the reasons why teachers use the storytelling method using flash card media for elementary school students. This storytelling method is for teaching vocabulary to elementary students at the Raudhatus Shibyan Foundation. The research design used is narrative inquiry and qualitative research methods. Data was collected from this research was by means of interviews and documentation. So, the results of the interviews conducted with the teacher answered several research questions that had been previously prepared by the researcher. From the teacher’s answer, this storytelling method is very important as a learning method for elementary students, because this method can increase children’s vocabulary to be wider than before, as well as gain experience and knowledge from the teacher’s verbal explanations. From the findings of the interview session, the method used by the teacher is the storytelling method as teaching carried out in the classroom. One way is by using flash card media, the teacher can show flash card image media to students. Based on the data obtained during the process of teaching vocabulary through storytelling using flash cards, the response was very good, indicating that the story content used was a variation of the vocabulary taught based on the ability to convey vocabulary according to the students’ abilities. The integration of storytelling and flashcards resulted in a more dynamic learning environment and better understanding. Of vocabulary in context. This study makes a significant contribution to the field of English language teaching by providing empirical insights into how teaching strategies, particularly those combining visual aids and storytelling, can improve language learning outcomes. This study highlights the importance of using age-appropriate and engaging methods in vocabulary teaching, especially at the elementary level